UKRAINIAN FISCAL EQUALIZATION: DOES IT NEED AN IMPROVEMENT? - S. Slukhai (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2015)
The article states that existing economic and social differences between territories in Ukraine call for use of fiscal equalization instruments. The study shows that implementation of formula-based fiscal equalization has led to a virtually full equalization of differentials in subnational total public revenues and expenditures on the regional level. Findings presented give reasons for reviewing a current fiscal equalization procedure with regard to incorporating into equalization grant allocation formula fiscal incentives for subnational governments.